Main issues of functioning of the electricity market - Кuznetsov, Vitaliy; Kolb, Andrii; Kuznetsova, Alisa; Halushko, Dmytro; Rabota, Dmytro; Drozhdev, Eugene (My University, 2022)
Due to the development of market relations in the industry of electric energy supply, electric energy is considered to be the product which should comply with certain quality and market demands. The Law of Ukraine ―On electric energy market‖ as in force on 17.10.2020 defines clearly the legislative, economic, and organizational grounds of the energy supply market, regulate the relations in terms of production, transmission, distribution, purchase and sell, supply of electric energy to provide reliable and safe electric energy supply for consumers taking into consideration the consumers‘ interests, development of competitive relations, minimization of costs for electric energy supply, and minimization of negative environmental impact.
Keywords: electric energy; електрична енергія; quality coefficient; коефіцієнт добротності